The Role of Posyandu Cadres in Reducing Stunting in the Community - Muslimin; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
The general background stunting is a major health issue that threatens the quality of human resources in Indonesia. Specific background posyandu cadres play a crucial role in disseminating health information and educating mothers to prevent and reduce stunting in communities. Knowledge Gap: While previous research has focused on general health initiatives, there is limited evidence on the specific role of posyandu cadres in reducing stunting in rural areas. Aims this study to examine the role of posyandu cadres in reducing stunting rates in the local community. Results the findings demonstrate that posyandu cadres have successfully carried out their role by conducting regular health programs such as providing supplementary food, vitamin A, blood supplements for pregnant women, and monitoring child growth. These efforts have contributed to a steady decrease in stunting rates. Factors influencing the success of the programs include the knowledge and active participation of trained cadres, high community involvement, and support from local health workers and officials. Novelty this study highlights the importance of community-based health initiatives and posyandu programs in addressing stunting, emphasizing the need for well-trained cadres in achieving long-term health outcomes. Implication the research underscores the importance of continuing support for posyandu cadres through training and resources to further improve public health and reduce stunting rates in other regions. Highlights: Posyandu cadres are key in reducing stunting through regular health activities. Knowledgeable and trained cadres contribute to lower stunting rates. Local community and health worker support strengthen program success. Keywords: Stunting, Posyandu Cadres, Community Health, Child Nutrition, Rural Development